Welding metallurgy and weldability - Lippold, John C. (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
"This book describes the weldability aspects of many structural materials used in a wide variety of engineering structures, including steels, stainless steels, Ni-base alloys, and Al-base alloys. The basic mechanisms of weldability are described and methods to improve weldability are described. Specific topics include solidification and liquation cracking, solid-state cracking, hydrogen cracking, fracture and fatigue, and corrosion. Methods for interpretation of weld failures using computational and characterization techniques are described"--
"Book deals with a wide range of materials and weldability issues"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Stainless steel -- Weldability; Stainless steel -- Metallurgy; Nickel -- Weldability; Nickel -- Metallurgy; Nickel alloys -- Weldability; Nickel alloys -- Metallurgy; TECHNOLOGY & ENGINEERING -- Material Science; Electronic books; Electronic books